Analysis of fluid flow across a 2D bluff body in a tandem arrangement with varying aspect ratios near a moving wall - Kumar Pant, Pawan; Chamoli, Sunil; Pant, Naval; Joshi, Hitesh; Rana, Saurav; Kumar Pathak, Manoj; Chuwattanakul, Varesa; Eiamsa-ard, Smith (Frontiers in Mechanical Engineering, 2026)
This study numerically investigates the flow characteristics around single and tandem cylinders positioned in close proximity to a moving wall at a Reynolds number of Re = 100. Using the finite volume method, simulations were performed for aspect ratios (AR) ranging from 1 to 5, while maintaining a fixed gap ratio (G/A = 0.5) and spacing ratio (S/A = 0.5). The results demonstrate that the moving wall significantly influences flow dynamics and stabilizes the wake. For an aspect ratio of 1, the merging of shear layers leads to the formation of elongated, steady vortices. As the aspect ratio increases from 2 to 5, the wake becomes increasingly smooth and the magnitude of positive vortices decreases, resulting in steady wake formation without significant oscillations. Force analysis reveals that the upstream cylinder exhibits chaotic drag (Cd) and lift (CL) coefficients, whereas the downstream cylinder shows a consistent trend. Notably, the upstream cylinder maintains a higher drag coefficient than the downstream cylinder, with both being lower than that of a single isolated cylinder. The observed suppression of vortex shedding is primarily attributed to the interaction and coupling of shear layers between the moving wall and the cylinders, identifying shear alignment rather than viscous damping as the core mechanism of wake control.